2013
DOI: 10.1002/chem.201302396
|View full text |Cite
|
Sign up to set email alerts
|

Selective Aerobic Oxidation of Methanol in the Coexistence of Amines by Nanoporous Gold Catalysts: Highly Efficient Synthesis of Formamides

Abstract: Holey gold: Highly selective aerobic oxidation of methanol over alkylamines was achieved with a reusable nanoporous gold (AuNPore) catalyst that was fabricated from a Au-Ag alloy. This excellent chemoselectivity enabled direct N-formylation of alkylamines from a mixture of methanol and amines. The remarkable catalytic activity was attributed to the synergistic effect between gold and the residual silver remaining in the AuNPore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 86 publications
(38 reference statements)
2
47
0
Order By: Relevance
“…The catalytic direct synthesis of amides from a mixture of an alcohol and an amine through selective oxidation of the alcohol is challenging because both functional groups are easily oxidized under ordinary oxidative conditions . We reported that the nanoporous gold behaves as a quite effective catalyst for the direct N‐formylation of amines with methanol . Treatment of a solution of octylamine in methanol at 60°C under oxygen and in the presence of an AuNPore catalyst derived from Au 30 Ag 70 alloy resulted in the formation of the formylated product in 97% yield (Table , entry 1).…”
Section: Nanoporous Metalsmentioning
confidence: 68%
See 1 more Smart Citation
“…The catalytic direct synthesis of amides from a mixture of an alcohol and an amine through selective oxidation of the alcohol is challenging because both functional groups are easily oxidized under ordinary oxidative conditions . We reported that the nanoporous gold behaves as a quite effective catalyst for the direct N‐formylation of amines with methanol . Treatment of a solution of octylamine in methanol at 60°C under oxygen and in the presence of an AuNPore catalyst derived from Au 30 Ag 70 alloy resulted in the formation of the formylated product in 97% yield (Table , entry 1).…”
Section: Nanoporous Metalsmentioning
confidence: 68%
“…Although the catalytic activity of AuNPore‐c was very low (entry 3), AuNPore‐d exhibited an enhanced catalytic activity (entry 4) comparable to that of AuNPore‐b (entry 2). These results indicate that the residual silver has an inhibiting effect in this process, which is completely opposite the effect in the aforementioned direct N‐formylation reaction …”
Section: Nanoporous Metalsmentioning
confidence: 99%
“…The answer is 'yes.' This led authors 36 to perform detailed study in the oxidation of methanol. Although it has been described in previous section that methanol could undergo gas-phase oxidation to methyl formate, the liquid-phase oxidation and trapping of intermediate obtained from methanol would be of great synthetic value.…”
Section: Methodsmentioning
confidence: 99%
“…Gold catalysts, known for their low‐temperature oxidation potential, high selectivity, and non‐toxic nature have proven ideal candidates 2b. 12 Accordingly, the oxidative coupling of alcohols and amines by colloidal gold systems (gold nanoparticles stabilized by, e.g., polyvinylpyrrolidone13 or DNA14), supported gold systems (on titania),15 and unsupported monolithic gold16 has been investigated. Yet, mechanistic understanding and, hence, directed catalyst design are lacking.…”
Section: Methodsmentioning
confidence: 99%